Environmental health and traditional fuel use in Guatemala - Ahmed, Kulsum, 1964- (Washington, D.C. : World Bank, 2005)
"Guatemala has a wealth of experience implementing improved stove programs. Through case studies, this book explores how this experience can be better targeted to reduce adverse health impacts of exposure to indoor air pollution and improve market structure and accessibility to cleaner fuels. A number of cross-sectoral interventions are recommended to ensure availability of information, improve monitoring of the coordination among stakeholders, facilitate the use of technical mitigation options, and promote long-term behavioral change. The health implications on morbidity and mortality cases of children under five years of age due to the failure to address the health impacts of IAP, either through policy interventions and/or technical mitigation measures, are estimated." "This book will be of interest to those interested in the environment, energy, public health, and socioeconomic development."--BOOK JACKET.
1. Introduction -- 2. Indoor air pollution and health : evidence from the demographic and health survey and the living standards measurement study -- 3. Estimating health impacts -- 4. The evolution of improved stoves in Guatemala : lessons from three programs -- 5. The role of LPG -- 6. Policy recommendations.
Includes bibliographical references and index.
Keywords: Environmental health -- Guatemala